A fresh look at Systems Engineering – what is it, how should it work?. Issue 1 (16th August 2018) - Sillitto, Hillary; Griego, Regina; Arnold, Eileen; Dori, Dov; Martin, James; McKinney, Dorothy; Godfrey, Patrick; Krob, Daniel; Jackson, Scott
Abstract: INCOSE's definition of SE was compared to the aspirations set out in SE Vision 2025 for SE as it ought to be to address modern challenges. Doing this led us to three fundamental realisations. First, while "20 th century systems" were, for the most part, "deterministic" or nearly so, 21 st century systems are on the other hand increasingly non‐deterministic, adaptive or "evolutionary". Second, while "20 th Century Systems Engineering Management" was implicitly based on a "command and control" paradigm, 21 st Century Systems Engineering, to be successful, will usually need to use a more collaborative leadership paradigm. And third, that while 20 th Century systems were largely "single systems", designed to "solve" specific problems, 21 st Century systems are almost invariably networked, and are parts of complex extended enterprises with multiple, often conflicting, stakeholder objectives, that are intimately related to complex societal challenges. We used elements of Soft Systems Methodology (SSM) to understand the implication and consequences of the paradigm shift implied by these realisations. A revised strawman definition of Systems Engineering is offered for consideration by INCOSE, showing the changes that would be required to take these and related factors into account.